PERTANGGUNGJAWABAN NOTARIS DALAM PERKARA PIDANA BERKAITAN DENGAN AKTA YANG DIBUATNYA MENURUT UNDANG-UNDANG NOMOR 2 TAHUN 2014 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 30 TAHUN 2004 - AHMAD REZA ANDHIKA (PREMISE LAW JURNAL, 2016)
DOSEN PEMBIMBING:Muhd Yamin Budiman GintingSyahril Sofyan Notary is a public official appointed by Government to help the society make present or emerging agreements in the society. The purpose of the making of these written agreements before a Notary is to guarantee the legal certainty of stakeholders of the agreements. The written agreement made before a Notary is called a Deed. The purpose of the Deed is, so that it can be used as powerful evidence in case of disputes among the stakeholders or any lawsuit from other parties. Based on this explanation, how important the function of the deed is obvious, thus, in order to prevent the deed from being invalid, Notary Public Institution is governed in Notary regulations which have been replaced by Law No 30/2004 on The Position of Notary. Keywords: Notary, Deed, Criminal Case